The Role of Fintech (Financial Technology) in the Mobile Banking-Based Non-Cash Payment System (Actionspay) in Islamic Microfinance Institutions - Eny Latifah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the role of using financial technology in a non-cash payment system based on mobile banking with the ActionsPay application at KSPPS BMT Bina Ummat Sejahtera Islamic Microfinance Institutions. This research method uses a descriptive qualitative approach with data analysis techniques by combining data triangulation: observation, documentation and interviews to obtain information and data to obtain results that are in accordance with the facts. The results of the study show that the role of fintech in the non-cash payment system is (1) Facilitating access to checking savings balances both before and after non-cash payments, (2) Accelerating the performance of Islamic Microfinance Institutions in knowing transactions that take place at any time when non-cash payments occur. cash, (3) Become a media and facilitator for Islamic Microfinance Institutions in providing services to non-cash payment system users, and (4) Encouraging the government to implement green economy, especially in efforts to reduce the use of paper and ink in the operations of Islamic Microfinance Institutions.